Comparison of Analgesic Effectiveness of Tapentadol and Tramadol in Relieving Postoperative Pain in Patients Undergoing Laparoscopic Cholecystectomy Under General Anesthesia: Tapentadol and Tramadol in Laparoscopic Cholecystectomy - Mohsin, Abdullah; Zaman, Muhammad Haris; Ali, Azib; Chouhdary, Zunaira Ayesha; Iqbal, Adnan; Younis, Adeel; Kanwal, Sibgha; Waseem, Humaira (Pakistan Journal of Health Sciences, 2025)
Various pharmacological interventions have aimed to address postoperative pain, however the search for optimal preemptive analgesic continues. In this assessment, it was sought to evaluate tapentadol and tramadol as preemptive analgesic, in order to identify the more effective option for managing postoperative pain. Objective: To compare the analgesic effectiveness of tapentadol and tramadol in relieving postoperative pain in patients undergoing laparoscopic cholecystectomy under general anesthesia. Methods: This quasi experimental study was conducted at Anesthesia Department of Mayo Hospital, Lahore from 30-11-2022 to 30-05-2023 after taking ethical approval from IRB. 60 individuals were enrolled after taking written informed consent, who were planned for laparoscopic cholecystectomy under general anesthesia. Patients were assigned to either group A (tramadol) or group B (tapentadol). Analgesic effectiveness was assessed in terms of time to first rescue analgesia, total rescue analgesic consumption in 24 hours, and VAS score at different interval postoperatively. Results: Mean time to 1st analgesia requirement calculated was 1.667±0.365 hours for group A and 4.46±1.45 hours for group B; p <0.0001. Mean total rescue analgesic (injection nalbuphine) consumption in group A and group B was 17.06±5.16mg and 8.4 ± 2.59mg, respectively (p <0.001). Mean of VAS score at different intervals noted was less in group B as compared to group A postoperatively, p <0.001. Conclusions: The findings of this study demonstrate that tapentadol 75 mg is more effective than tramadol 50 mg as preemptive analgesia in patients undergoing laparoscopic cholecystectomy.